Immunotropic effects of nitrogenous metabolites in patients with chronic pyelonephritis - Kuchma, Igor; Gozhenko, Anatoliy; Flyunt, Igor-Severyn; Ruzhylo, Sofiya; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2021)
Background. We have previously shown that nitrogenous metabolites have immunomodulatory effects in healthy rats and humans as well as in patients with encephalopatia. The purpose of this study is their immunotropic activity in patients with chronic pyelonephritis. Materials and Methods. The object of observation were 24 men (aged 23-76 years) with chronic pyelonephritis in remission. The plasma levels and urinary excretion of uric acid, urea and creatinine and parameters of immunity twice (on admission and after 10 days of balneotherapy at the Truskavets’ Spa) was performed. Results. Judging by the multiple correlation coefficient uricemia exhibits maximal immunotropic activity (R=0,772), followed by creatininemia (R=0,643), urea plasma (R=0,584) and creatinineuria (R=0,506) instead, urea and uric acid excretion correlate with immune parameters insignificantly (R=0,327 and 0,262 respectively). Nitrogenous metabolites together upregulate most parameters of phagocytosis by neutrophils Staph. aureus and E. coli, the level in the blood of CD8 T-lymphocytes, CIC, IgM, componentes of leukocytogram as well as entropy of leukocytogram and immunocytogram. Instead, they downregulate the relative level of lymphocytes in general and of CD4 T-lymphocytes in particular. Conclusion. Nitrogenous metabolites exhibit immunotropic activity in both healthy humans and in patients with chronic pyelonephritis in remission. Both common and distinctive features of immunomodulation were revealed.